2017
DOI: 10.21834/e-bpj.v2i6.988
|View full text |Cite
|
Sign up to set email alerts
|

Land Registration of Titles at Stake: West and East Malaysia Compared

Abstract: Registration of land title evidences an indefeasible ownership. However, many people have become victims of fraud. Due to the increase in fraud and the weaknesses of the registration system in the country, this study aims to provide solution to the problem. The paper highlights the controversy surrounding indefeasibility and the concept of federalism in the land administration systems in Malaysia. The electronic land systems and fraud prevention measures in the country are also analysed. While other jurisdicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Among the most common occurrences is the falsification of: original court order, identification card, issue document of title (IDT), power of attorney, signature, and transfer form (Form 14A), besides impersonating as an estate agent or as an occupant. Abdullah (2017) in her article has concluded that the number of cases concerning fraud involving title registration in Malaysia is not showing any decline. She surmises that it sufficiently proves that the title registration system in Malaysia is susceptible to fraud.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most common occurrences is the falsification of: original court order, identification card, issue document of title (IDT), power of attorney, signature, and transfer form (Form 14A), besides impersonating as an estate agent or as an occupant. Abdullah (2017) in her article has concluded that the number of cases concerning fraud involving title registration in Malaysia is not showing any decline. She surmises that it sufficiently proves that the title registration system in Malaysia is susceptible to fraud.…”
Section: )mentioning
confidence: 99%
“…It can even be followed by certificate duplication and/or certificate forgery, or other combinations of actions known as fraud. Fraud in the title register often creates concern for house owners as it is a breach of property rights (Abdullah et al, 2017). Among the most common occurrences is the falsification of: original court order, identification card, issue document of title (IDT), power of attorney, signature, and transfer form (Form 14A), besides impersonating as an estate agent or as an occupant.…”
Section: )mentioning
confidence: 99%
“…The main cause of increasing fraud cases is vulnerabilities in the current registration system at the Land Office, which can be exploited by attackers. Therefore, there is a need to ensure that the registration system is secure, safe, reliable, and fraud-proof [15].…”
Section: What Are the Challenges And Defects In The Land Registry System In Malaysia?mentioning
confidence: 99%
“…This proves the injustice of the current system judgment on the innocent purchaser. Abdullah et al [15] conducted a study on indefeasibility and the concept of federalism in Malaysia's land administration system. From their study, they found an increasing number of cases regarding title registration fraud in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many citizens tend to suffer from fraud. Because of the rising number of fraud and the poorness of the registration system in the country, the current research has the objective of providing a solution to the mentioned issue [3].…”
Section: Introductionmentioning
confidence: 99%